2022
DOI: 10.3389/fendo.2022.898471
|View full text |Cite
|
Sign up to set email alerts
|

Distinct impacts of fat and fructose on the liver, muscle, and adipose tissue metabolome: An integrated view

Abstract: ObjectiveIn the last years, changes in dietary habits have contributed to the increasing prevalence of metabolic disorders, such as non-alcoholic fatty liver disease (NAFLD) and type 2 diabetes mellitus (T2DM). The differential burden of lipids and fructose on distinct organs needs to be unveiled. Herein, we hypothesized that high-fat and high-fructose diets differentially affect the metabolome of insulin-sensitive organs such as the liver, muscle, and different adipose tissue depots.MethodsWe have studied the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 81 publications
1
8
0
Order By: Relevance
“…A HFrD induced more liver inflammatory degeneration and hence further promoted MASH compared to a HFD which induced more liver steatosis. 60 This pro-inflammatory role of fructose was reinforced by a reported association with higher muscle levels of interleukin (IL)1α. 61 Both a HFrD and a HFD promote IR in the liver and skeletal muscle by impairing the insulin signalling pathway.…”
Section: Pathophysiology Of Myosteatosis In Masldmentioning
confidence: 99%
See 2 more Smart Citations
“…A HFrD induced more liver inflammatory degeneration and hence further promoted MASH compared to a HFD which induced more liver steatosis. 60 This pro-inflammatory role of fructose was reinforced by a reported association with higher muscle levels of interleukin (IL)1α. 61 Both a HFrD and a HFD promote IR in the liver and skeletal muscle by impairing the insulin signalling pathway.…”
Section: Pathophysiology Of Myosteatosis In Masldmentioning
confidence: 99%
“…In the same way that diet causes steatosis, consumption of a high-fructose (HFrD) or a high-fat diet (HFD) is associated with myosteatosis. [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] According to tracer experiments, the most important source of lipids in the steatotic liver is the insulin-resistant adipose tissue. 64 It is therefore logical to assume that FFAs from the adipose tissue also contribute to myosteatosis.…”
Section: Pathophysiology Of Myosteatosis In Masldmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of the BAT weight shown in our experiment could be related to beneficial outputs, but the increase of BAT did not necessarily imply an increase of its activity, which is what several researchers highlighted in their works. 33,34 The authors reported that fructose intake could impair the potential of the tissue for glucose uptake and thermogenesis, which was related to fructose-induced metabolism.…”
Section: Food and Function Papermentioning
confidence: 99%
“…2,27,31,34,37 Some of the authors reported >5% of the hepatic fat content analyzed by H&E stain as an expression of NAFLD with high fructose consumption, due to the activation of the lipogenic pathway and the absence of a regulatory mechanism of fructose metabolism, as fructolysis is an insulin-independent process. 34 Moreover, they suggested that the activation of lipogenic pathways is time and dose dependent, but other factors could explain why other researchers did not see the lipogenic effect in their experiment, 38 with the lack of the expected results related to the degree of stress experienced by the animals. Thus, although the hepatic fat content of the livers from F was lower than 5%, our results suggest an increasing fat deposition in the livers of rats that were supplemented with 30% fructose in drinking water for 10 weeks.…”
Section: Food and Function Papermentioning
confidence: 99%